Epithelial surfaces of the trachea and principal bronchi in the rat. Issue 2 (April 1975) - Alexander, I; Ritchie, B C; Maloney, J E; Hunter, C R
Abstract : The epithelial surfaces in the trachea and principal bronchi of healthy rats were examined by scanning electron microscopy. A system of four cell types, ciliated, microvillous, brush, and goblet cells, in this order of frequency, were found and intermediate type cells were not seen. An extensive area of the surface examined was covered by densely ciliated epithelium. The presence of other cell types beneath the cilia was confirmed by transmission electron microscopy. Areas up to 1 mm in diameter and randomly distributed were observed where microvillous cells predominated and only occasional ciliated cells were found. Most ciliated cells in these areas were adjacent to glandular openings or goblet cells. The larger microvilli of the brush cells were arranged in a coronal configuration elucidated by the scanning electron microscope. Preparatory techniques recently introduced for the examination of soft tissue in the scanning electron microscope facilitated the confirmation of cell types present and the microarchitecture of the epithelial surface.